What does black-body radiation mean for pre-service physics teachers? Research Article - Bezen, Sevim; Aykutlu, Işıl; Bayrak, Celal (Journal of Turkish Science Education, 2021)
This study aims to determine pre-service teachers’ conceptual understanding of black-body radiation. Designed as a qualitative study, it was realized by employing a case study, which is one of the descriptive research methods. The study group consists of 18 pre-service teachers enrolled as seniors. An opinion form and a concept map were used as data collection tools. In other words, results were intended to be comparatively examined by using two different qualitative data collection methods. Pre-service teachers’ answers were analysed with the help of answer sculptures. At the end of the study, it was determined that while pre-service teachers generally have the correct conceptual structure, they still have some specific points. It was seen that pre-service teachers have problems with understanding especially the Wien law and electromagnetic radiation taking place in black-body radiation.